Risk Assessment of Exposure to Preservative, Synthetic Organic Dyes and Microorganisms from the Consumption of Processed meat in Trang Province - เรืองขำ, อลิสรา; วัฒนสิน, พัชรินทร์ (Journal of Health Science of Thailand, 2021)
Risk assessment of exposure to preservative, synthetic organic dyes and microorganisms from the consumption of processed meat in Trang Province . 30 samples were analyzed for benzoic acid, sorbic acid, synthetic color, nitrate, nitrite, Staphylococcus aureus and Salmonella spp. The results show two samples (6.6%) were found benzoic acid in the samples of Chinese sausage and Thai East sausage, the amount of benzoic acid were in the range of 67.6 - 227.4 mg/kg. On synthetic color analyzed ; Two Sausages (6.6%) were found erythrosine, the amount of erythrosine were in the range of 2.4 - 7.8 mg / kg. and one Sausage (3.3%) was found Tartrazine for 2.2 mg/kg . One Sausage (3.3%) was found nitrate for 1,085 mg / kg. And six samples (20%) were found nitrite. There are two sausages, three hams and a Thai East sausage, the amount of nitrite were in the range of 17.3 -54.1 mg/kg . No contamination were found for Staphylococcus aureus and Salmonella spp. All data are used to estimate the exposure assessment from the intake of benzoic acid, sorbic acid, synthetic color, nitrate and nitrite at the average and 95 percentile of eater only and per capital found that benzoic acid, synthetic color and nitrate in all food samples had no risk of damage to health. While nitrite in sausages ham and Thai East sausages exposure assessment for age 3 – 5.9 year which are at risk of damage to health as same as exposure assessment nitrite in sausages for age 6 – 34.9 year.